HYDROTHERMAL SYNTHESIS OF NITROGEN-DOPED CQDS OF RUBUS NIVEUS LEAVES FOR FLUORESCENT pH SENSING AND PHOTOCATALYTIC APPLICATIONS - Poonam Negi,; Rawat, B.S.; Naveen Chandra Joshi,; W. Ahmad,; Narinder Kumar,; S. Upadhyay,; K. P. S. Parmar,; R. Saxena,; R. Dhyani,; P. S. Khati,; A.S. Rana, (Malaysian Journal of Science, 2024)
The development of a fluorescent pH sensor and the treatment of wastewater with nanoparticles are both critical topics. The variation in pH impacts the morphology and subsequent properties of the nanoparticles, which are used for their utilization in various fields and the second one gives a better treatment approach for industrial waste entities. The present study examines the effects of these variables on the biologically produced nitrogen-doped carbon quantum dots (NCQDs). Hydrothermal process was performed for the synthesis of the same by using Rubus-niveus leaf extract as a precursor. The UV-Vis spectroscopy analysis shows absorption spectra in the wide range of 200 nm to 800 nm and shows prominent peaks at 236 nm and 392 nm, respectively. Further, the direct energy band gap of 3.65eV was analysed for NCQDs. The SEM image shows flower-shaped particles, and FT-IR analysis indicates the existence of amide, CHO, N-H, and C-N functional groups. XRD pattern showed that the surface morphology of NCQDs is amorphous in nature. A good response was found in the variation of fluorescence intensity with the pH values, confirming the possibility of NCQDs serving as pH sensors. Rhodamine-B (Rh-B) dye's reaction kinetics was revealed for the purpose of analyzing the potential of NCQDs for the degradation of commercial dyes and found to be followed by pseudo-first order kinetics with the correlation coefficient of 0.80.